A-16 Gender Differences and Composite Scores Performance at Baseline. (13th July 2022) - Gilmore, M; Lashley, L; Golden, C
Abstract: Purpose: To examine whether there are gender differences in symptomatology reported at baseline testing in individuals who did not report a prior concussion history, diagnosis of ADHD, dyslexia, autism, headaches, psychiatric conditions, substance abuse, and epilepsy at baseline using ImPACT. Methods: Participants were selected from an archival de-identified sports medicine ImPACT baseline database. The sample (n = 1898) consisted of adolescent high school athletes, primarily male (60.8%) in South Florida (mean age = 15.35 years, SD = 1.09). An independent samples t-test was conducted to determine the relationship between gender and composite score performance at baseline. All analyses were conducted at p < 0.05. Results: The independent samples t-test revealed significant differences (p < 0.001) between genders on verbal memory and impulse control composite scores, but not visual memory, visual motor speed, and reaction time. Conclusions: Females performed significantly better on the overall measure of verbal memory which is consistent with previous studies (Cottle et al., 2017; Covassin et al., 2006). This may be due to female athletes exerting more effort or taking baseline testing more seriously (Cottle et al., 2017). Female athletes exhibited more control on impulse control, a task where quick and accurate decision making is required. Significant differences were not found in reaction time, visual memory, and visual motor speed which is not in line with previous studies. This may be due to the version of ImPACT used. Previous studies were conducted using version 2.0 or 2.1, while this study was conducted with versions 4.1 and 4.2. As ImPACT was updated, the new versions may have become less sensitive to differences in gender.